Association of adrenal insufficiency with patient-oriented health-care outcomes in adult medical inpatients. Issue 6 (December 2019) - Ebrahimi, Fahim; Widmer, Andrea; Wagner, Ulrich; Mueller, Beat; Schuetz, Philipp; Christ-Crain, Mirjam; Kutz, Alexander
Abstract : Objective: Adrenal insufficiency in the outpatient setting is associated with excess morbidity, mortality, and impaired quality of life. Evidence on its health-care burden in medical inpatients is scarce. The aim of this study was to assess the health-care burden of primary adrenal insufficiency (PAI) and secondary adrenal insufficiency (SAI) among hospitalized inpatients. Design and methods: In this nationwide cohort study, adult medical patients with either PAI or SAI hospitalized between 2011 and 2015 were compared with propensity-matched (1:1) medical controls, respectively. The primary outcome was 30-day all-cause in-hospital mortality. Main secondary outcomes included ICU admission rate, length-of-hospital stay, 30-day and 1-year all-cause readmission rates. Results: In total, 594 hospitalized cases with PAI and 4880 cases with SAI were included. Compared with matched controls, in-hospital mortality was not increased among PAI or SAI patients, respectively. Patients with adrenal insufficiency were more likely to be admitted to ICU (PAI: OR 1.9 (95% CI, 1.27 to 2.72) and SAI: OR 1.5 (95% CI, 1.35 to 1.75)). Length of hospital stay was prolonged by 1.0 days in PAI patients (8.9 vs 7.9 days (95% CI, 0.06 to 1.93)), and by 3.3 days in SAI patients (12.1 vs 8.8 days (95% CI, 2.82 to 3.71)), when compared with matched controls. Patients with SAI were found to have higher 30-day and 1-year readmission rates (14.1 vs 12.1% and 50.0 vs 40.7%; P < 0.001) than matched controls. Conclusions: While no difference in in-hospital mortality was found, adrenal insufficiency was associated with prolonged length of hospital stay, and substantially higher rates of ICU admission and hospital readmission.